Piil Pesenggiri Local Wisdom as the Base of Character Education in Social Studies Learning at Metro City Elementary School, Lampung - Afriyadi, Muhammad Muchsin; Widiati, Utami; Arifin, Imron; Ramli, M.; Maba, Aprezo Pardodi (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2024)
This study explores the integration of Piil Pesenggiri local wisdom into character education through Social Sciences Subject (IPS) in elementary schools in Metro City, Lampung. Piil Pesenggiri local wisdom, which consists of four main pillars; respect for others (Nemui Nyimah), cooperation (Sakai Sambayan), achievement (Juluk Adek), and equality (Nengah Nyampur), has been recognized as an important foundation for strengthening character learning in the school environment. This study utilizes qualitative approach and case study in three different elementary schools in Metro City. The research method used is multi-case skin, which collects data through in-depth interviews, participatory observations, and analysis of learning documents. The results depict that the application of Piil Pesenggiri values in social sciences subject significantly promoted positive characters development among learners, including respect for diversity, cooperation, motivation for achievement, and understanding of equality. This practice not only enriches the social sciences subject’s curriculum with culturally relevant content but also contributes to the formation of positive social attitudes and behaviors among learners. These findings suggest that local wisdom such as Piil Pesenggiri can be used as an effective instrument in character education, supporting a holistic vision of education in Indonesia, especially in the diverse community contexts such as Metro City, Lampung. This research provides important insights into the potential of local wisdom in forming the basis of strong and culturally relevant character education.